Role of Water Soluble Carbohydrates in Improving Drought Stress Tolerance in Wheat: An Overview - Gaur, Arpit; Sharma, Deepti; Sheoran, Sonia; Chahal, Sulekha; Chaudhary, Kaveri; Singh, Gyanendra; Singh, Gyanendra Pratap (Journal of Cereal Research, 2022)
Abiotic factors such as drought and heat stress impairs photosynthetic assimilates, shortening the carbon supply to the developing grains leads to yield loss. Under water stress, stem water-soluble carbohydrates (WSCs) mainly fructans, play an important role in buffering yield during the grain filling period in wheat. The stem WSCs may contribute up to 20% of the total dry weight of grain under irrigated conditions and upto 70% of grain dry matter under drought stress. Additionally, it maintains physiological balance under water-stressed conditions by acting as signalling molecules to various phytochemicals and hormones. Therefore, this drought adaptive trait can be a potential breeding target for sustainable wheat production, especially for water limiting conditions. Despite the proven contribution of stem WSCs to water-stress tolerance in wheat and compensating grain yield, a comprehensive review on this trait is still missing in the literature. With this review, efforts are made to compile the available information on the physiological, genetic and molecular aspects of accumulation and remobilisation of stem WSCs to bring more attention of plant scientists to this trait. Furthermore, effective molecular marker systems such as KASP to target stable loci identified using GWAS, QTL or meta-QTL studies may bring precision to the selection and accelerate the WSCs based wheat breeding program.